Brounea, a new genus (Coleoptera: Staphylinidae: Pselaphinae) from New Zealand, with descriptions of nine new species - Park, Jong-Seok; Carlton, Christopher E. (Zootaxa, 2015)
A new genus and nine new species of New Zealand endemic pselaphine staphylinid beetles belonging to the supertribe Faronitae are described: Brounea Park & Carlton, gen. nov. (type species: Sagola setiventris Broun, 1915); B. yoonhoi Park & Carlton, sp. nov., B. chorui Park & Carlton, sp. nov., B. sungryongi Park & Carlton, sp. nov., B. mijeongae Park & Carlton sp. nov., B. seongmoi Park & Carlton sp. nov., B. daehyuni Park & Carlton sp. nov., B. mangamukaensis Park & Carlton sp. nov., B. sunjaei Park & Carlton sp. nov., and B. seungili Park & Carlton sp. nov. Two species, S. setiventris and S. tenuis Broun, 1886, are transferred to the genus Brounea. A key to species, habitus photographs, and line drawings of diagnostic characters are provided.